Chemical constituents and their biological activity of Pinus dalatensis. Part 1. Terpenoids from the leaves - Sa, Nguyen Hoang; Tam, Nguyen Thanh; Quan, Tran Duc; Tinh, Bui Xuan; Thien, Dao Duc; Sung, Tran Van; Adorisio, Sabrina; Delfino, Domenico V (Vietnam Journal of Chemistry, 2017)
Seven terpenoids were isolated from the dried leaves of Pinus dalatensis Ferré, including one caryolane sesquiterpenoid (1), five labdane diterpenoids (2, 3, 4, 5, 6) and one serratane triterpenoid (7). The structures of the isolated compounds were determined on the basic of spectroscopic methods (ESI-MS, NMR) and comparison with reported data. Among these compounds, the mixture of compounds 2 and 3 showed inhibitory effects on the growth of acute myeloid leukemia (OCI-AML) cells. This is the first report on the chemical compositions of Pinus dalatensis in Vietnam. Keywords. Pinus dalatensis, serratane triterpenoid, caryolane sesquiterpenoid, labdane diterpenoid, acute myeloid leukemia, antiproliferative effect.